Sensitive screening tests for suspected class A carbapenemase production in species of Enterobacteriaceae - Pasteran, Fernando (2009)
Fil: Pasteran, Fernando. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Bacteriología. Servicio Antimicrobianos; Argentina.